Muscarinic acetylcholine receptor activated effectors in principal neurons of the rat basolateral amygdala - Sahagian, Todd J.; Harden, Scott W.; Bizon, Jennifer L.; Setlow, Barry; Frazier, Charles J. (Frontiers in Cellular Neuroscience, 2025)
The basolateral amygdala (BLA) plays a crucial role in context-specific learning and memory by integrating valence-specific stimuli with internal physiological states. Cholinergic signaling systems modulate neural excitability to influence information processing in the BLA. Muscarinic acetylcholine receptors (mAChRs) are of particular interest because aberrant mAChR signaling in BLA circuits is associated with neuropsychiatric disorders, cognitive impairment, substance use, and age-related cognitive decline. This study evaluates mAChR activation in BLA principal neurons (PNs) in juvenile rat brain slices using whole-cell patch-clamp recordings. We found that bath application of carbachol (CCh) produces a pirenzepine sensitive excitatory response in BLA PNs voltage clamped near the resting potential, which depends on an underlying biphasic change in membrane resistance, indicating an involvement of multiple effectors. More specifically, we observed that CCh excites BLA PNs by inhibiting the afterhyperpolarization (AHP), by reducing a steady state inhibitory current, and by promoting an afterdepolarization (ADP). We further identify and characterize a CCh-induced and calcium-activated non-selective cation current (ICAN) that underlies the ADP in voltage clamp. Overall, our findings provide new insights into specific effectors modulated by activation of pirenzepine sensitive mAChRs expressed by BLA PNs. We also reveal new details about the time- and voltage-dependence of current carried by the CCh -activated ICAN like current in BLA PNs, and highlight its ability to promote a suprathreshold ADP capable of generating sustained firing after a brief excitatory stimulus. Improved understanding of these effectors will provide potentially valuable new insights on the wide range of mechanisms through which cholinergic system dysfunction can lead to impaired executive function.